2022
DOI: 10.1177/15280837221078535
|View full text |Cite
|
Sign up to set email alerts
|

Omniphobic polyurethane – superabsorbent polymer – fluoropolymer surface coating on cotton fabric for chemical protection and thermal comfort

Abstract: This research aims to develop chemical protective clothing via a functionalised surface coating on cotton fabric for simultaneous barrier performance and thermal comfort. An omniphobic protective layer on the cotton fabric was developed through a polyurethane – superabsorbent polymer – fluoropolymer coating to protect the penetration of water, oils and liquid chemicals. It was found that the padding of coated specimens with fluoropolymer provided a substantial improvement of hydrophobicity, and therefore, exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…[32,33] Recent studies have exploited this property for the facile and scalable spray coating of omniphobic, multi-leveled micro/nanostructures. For instance, the spray-coating of silanizing agents, [34,35] highly networked silver nanoflakes, [36,37] and a conformable fluoropolymer [38][39][40] has all been utilized in the textile industry to produce omniphobic and bacteria-repellent garments. However, their instability hinders their applicability for real-world applications.…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] Recent studies have exploited this property for the facile and scalable spray coating of omniphobic, multi-leveled micro/nanostructures. For instance, the spray-coating of silanizing agents, [34,35] highly networked silver nanoflakes, [36,37] and a conformable fluoropolymer [38][39][40] has all been utilized in the textile industry to produce omniphobic and bacteria-repellent garments. However, their instability hinders their applicability for real-world applications.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to bulk polymerization, solution polymerization makes it easier to control the temperature and molecular weight of the product. 16 Apart from the polyurethane-based coating studies with a coating paste containing powdered SAP, 17,18 no academic study has been found in the literature on water-based coating applications.…”
Section: Introductionmentioning
confidence: 99%